KUALITAS KAWASAN PANTAI DEPOK, GUMUK PASIR BARCHAN, PANTAI PARANGKUSUMO DAN PANTAI PARANGTRITIS BERDASARKAN PARAMETER GEOWISATA - , Primantoro Nur Vitrianto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The whole Parangtritis area has natural, culture, and special interest (culinary) tourism attraction, the attraction integrated as one tourism attraction potential, the full potential needs to be developed and preserved. Geotourism expected to become one of the alternative approaches in exploiting the potential of existing natural resources in all the Parangtritis area, which includes Depok beach, Barchan sand dunes, Parangkusumo beach, and Parangtritis beach, either in the form of enrichment increased insight into the uniqueness of a tourist attraction, increased understanding the process of natural physical phenomena (geomorphology), as well as improving the quality of human resources in the area. Geotourism has impacts to the development of employment in various sectors, such as transport, hotels and tour guides as well as spur economic growth as transport, hotels and tour guides as well as spur economic growth. The aim of this research is to understand the quality of Depok beach, Barchan sand dune, Parangkusumo beach, and Parangtritis beach area, based on geotourism parameters. Phenomenological approach used in this study, along with questionnaires and interviews with informants and field observation. Data analysis was done inductively with descriptive qualitative method. The results of this research show, that the quality of Depok beach, Barchan sand dune, Parangkusumo beach and Parangtritis beach areas based on geotourism parameters, is good. However, if traced further, the area that has the highest quality is Depok Beach area with a value of 4:14 (maximum scale of 5.00), the second is Parangtritis beach area occupied by the value of 4:07, the third is Parangkusumo beach area with a value of 3.97, and the fourth is Barchan sand dunes with medium quality and the value of 3.30. Seafood culinary area is one of the tourism developments in Depok beach besides improving the quality and variety of cuisine, as well as the level of food hygiene. Barchan sand dunes area can be developed as an education/research tourism area based on the unique morphology of sand dunes. It is expected to preserve the environment, develop land use regulations (building restrictions), that is can interfere Aeolian processes that take place in the active area of sand dunes. Parangkusumo beach can be developed as an area of cultural and pilgrimage tourism, which those activities will become national tourism event. The tourism developments in Parangtritis beach focused on sustainable family tourism and provide protection for the preservation of art, culture and environment.